Online learning satisfaction in higher education: what are the determining factors? - Sri Suhandiah; Fendy Suhariadi; Praptini Yulianti; Ratna Wardani; Yurilla Endah Muliatie (Jurnal Cakrawala Pendidikan, 2022)
Covid-19 pandemic crisis has required the implementation of comprehensive online learning in Indonesia, including in the higher education institutions. Changes in the conventional way of face-to-face learning to online one provide both positive and negative responses, which will affect student learning satisfaction. This research aims to determine student satisfaction with the online learning which is associated with perceived technological complexity, student learning experience, online learning readiness, and presence of lecturers in online learning activities. This research employed a quantitative approach. Data were collected utlizing a google online questionnaire distributed through a network of lecturers. The samples were 439 students from state and private higher education institutions spreading across eight islands in Indonesia. Statistical analysis utilized the Structural Equation Model (SEM) in Stata 15. The results show that online learning satisfaction is positively influenced by student experience, online learning readiness, and the presence of lecturers in online learning. Moreover, online learning readiness can mediate student experience and online learning satisfaction but unable to mediate technology complexity and online learning satisfaction. These findings add to the literature on online learning satisfaction and provide direction for the solution of problems on online learning satisfaction. The proposed suggestion to higher education institutions is to encourage the development of online-based collaborative models and to provide a continuous experience for students.